Interleukin-33 Amplifies Human Mast Cell Activities Induced by Complement Anaphylatoxins - West, Peter W.; Bahri, Rajia; Garcia-Rodriguez, Karen M.; Sweetland, Georgia; Wileman, Georgia; Shah, Rajesh; Montero, Angeles; Rapley, Laura; Bulfone-Paus, Silvia (Frontiers in Immunology, 2021)
Both, aberrant mast cell responses and complement activation contribute to allergic diseases. Since mast cells are highly responsive to C3a and C5a, while Interleukin-33 (IL-33) is a potent mast cell activator, we hypothesized that IL-33 critically regulates mast cell responses to complement anaphylatoxins. We sought to understand whether C3a and C5a differentially activate primary human mast cells, and probe whether IL-33 regulates C3a/C5a-induced mast cell activities. Primary human mast cells were generated from peripheral blood precursors or isolated from healthy human lung tissue, and mast cell complement receptor expression, degranulation, mediator release, phosphorylation patterns, and calcium flux were assessed. Human mast cells of distinct origin express constitutively higher levels of C3aR1 than C5aR1, and both receptors are downregulated by anaphylatoxins. While C3a is a potent mast cell degranulation inducer, C5a is a weaker secretagogue with more delayed effects. Importantly, IL-33 potently enhances the human mast cell reactivity to C3a and C5a (degranulation, cytokine and chemokine release), independent of changes in C3a or C5a receptor expression or the level of Ca2+ influx. Instead, this reflects differential dynamics of intracellular signaling such as ERK1/2 phosphorylation. Since primary human mast cells respond differentially to anaphylatoxin stimulation, and that IL-33 is a key regulator of mast cell responses to complement anaphylatoxins, this is likely to aggravate Th2 immune responses. This newly identified cross-regulation may be important for controlling exacerbated complement- and mast cell-dependent Th2 responses and thus provides an additional rationale for targeting anti-IL33 therapeutically in allergic diseases.